ANALISIS BAYESIAN SURVIVAL WEIBULL UNTUK MENENTUKAN FAKTOR YANG MEMPENGARUHI LAJU KESEMBUHAN PASIEN RAWAT INAP KANKER SERVIKS DI RSDU KOTA MAKASSAR - Nini Harnikayani Hasa; M Nadjib Bustan; Aswi Aswi (Program Studi Statistika Fakultas MIPA UNM, 2022)
Survival analysis is a statistical procedure for analyzing data where the response variable is the time until the occurrence of an event. In this study, Bayesian survival Weibull was used to determine the factors that influence the rate of recovery of cervical cancer inpatients. The data used in this study is cervical cancer inpatient data at the Makassar City Hospital for the 2017-2019 period. Based on the results of the analysis, it was found that a significant factor affecting the healing rate of cervical cancer inpatients was complications. Cervical cancer inpatients who experience complications tend to recover slower by 0.258 than patients who do not experience complications.